Keterampilan Dasar Berbahasa Arab Melalui Strategi Pembelajaran Aktif - Rahmaini Rahmaini (Departement of Mathematics Education, 2023)
This study aims to examine basic skills in Arabic through active learning strategies. This is based on efforts to improve students' abilities from beginners (ibtida') to advanced (al-mahara). This research uses a qualitative approach with the method of literature study. The results of this study found that basic Arabic language skills through active learning strategies were divided into six, namely (1) mufradat (vocabulary) learning strategies, (2) tarkib learning strategies, (3) istima' (listening) learning strategies, (4) learning strategies learning kalam (speaking), (5) learning strategy qira'ah (reading), and (6) learning strategy kitabah (writing). Through this research, it is hoped that it will become a basic concept that can be recommended as a basis for learning Arabic from the beginner to advanced stages for students.